The Effect Of Blended Learning Model On Student Learning Outcomes In Class Viii Spldv Learning At SMP Negeri 4 Touluaan - Natasya Ngantung; Victor R. Sulangi; Anekke Pesik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study sought to examine and evaluate the average learning outcomes of students who received instruction in a system of two-variable linear equations using either the direct learning model or the blended learning model. The research employed the posttest-only control design. The participants in this study comprised of two groups: class VIII-A, an Experimental class consisting of 17 students, and class VIII-B, a control class consisting of 17 students at SMP Negeri 4 Touluaan. The data collected pertains to the posttest outcomes in both the Experiment and Control groups, indicating an average learning outcome of 85.29 for the Experiment group and 77.94 for the Control group. The normality test for the data is satisfied when the data follows a normal distribution. The study yielded results indicating a significant level of 0.05, with the obtained t-value of 1.89098 being greater than the critical t-value of 1.694. According to the findings of this study, students who engage in Blended Learning exhibit superior learning outcomes in the context of acquiring proficiency in solving systems of linear equations with two variables, as compared to students who rely solely on direct instruction.